REVIEW LITERATUR ANALISIS PENGARUH FAKTOR RISIKO TERHADAP KEJADIAN STUNTING PADA ANAK BALITA - Budi Kristanto (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background: stunting is the result of non-fulfillment of nutrients as per the terms ofnutrition in growth between the period of conception to age 24 months. Stunting reflectsthe accumulated growth retardation before and after birth. Failure of growth duringchildhood and often irreversible effect on adult life is short stature. The cause stuntingvery complex.Objective: the aim of this literature review to analyze the effect of risk factors on theincidence of stunting in children under five.Methods: the literature review conducted by Critical appraisal. The inclusion criteriainclude children with stunting, aged 0-59 months, have KMS, still have a father and amother. While exclusion criteria specified are children who do not have KMS, childrenwho have no parents. Data extracted from multiple sources and then synthesized into areview article from 6 different articles.Results: factor nutritional status and body weight â‰¥ 2,500 grams, socioeconomic for classC (poorest), aged 12-23 months, the duration of breastfeeding a child for 6-12 monthsand the mother's education with secondary and higher education have a significantinfluence on the incidence of stunting children (Ï-value = <0.001; <0.001; <0.001; <0.001;<0.002 and <0.008). Nutritional status and body weight â‰¥ 2,500 grams, socioeconomic forclass C (poorest) and the duration of breastfeeding a child for 6-12 months is a risk factorfor children to experience stunting, while the mother's education at secondary and highereducation is not a risk factor stunting of children ( OR = 0.83 and 0.73).Conclusions: social and economic factors are dominant factors on the risk of childrenexperiencing stunting (OR = 4.8).Keywords: stunting, toddler, risk factors